2009
DOI: 10.1111/j.1471-0528.2008.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of human papillomavirus vaccination among Chinese women: concerns and implications

Abstract: Objective To explore Chinese women's perceptions of human papillomavirus (HPV) vaccination and their intention to be vaccinated.Design A cross-sectional community-based survey study.Setting Thirteen community women's health centres of The Family Planning Association of Hong Kong.Sample A total of 1450 ethnic Chinese women aged 18 or above who attended the health centres.Methods Participants completed a written consent and an anonymous questionnaire onsite.Main outcome measures Knowledge and beliefs about HPV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 32 publications
(41 reference statements)
4
64
2
2
Order By: Relevance
“…The acceptability of HPV vaccination was relatively low among the medical undergraduates surveyed in this study. It was higher than among parents of young adolescents (<40.0%) (Chan et al, 2007;Zhang et al, 2013) , but relatively lower than among surveyed Chinese women (>80.0%) (Kwan et al, 2009;Li et al, 2009). The vast majority of students consented to HPV vaccination after 13 years and 38.0% of males and 50.7% of females suggested an age over 19 years.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The acceptability of HPV vaccination was relatively low among the medical undergraduates surveyed in this study. It was higher than among parents of young adolescents (<40.0%) (Chan et al, 2007;Zhang et al, 2013) , but relatively lower than among surveyed Chinese women (>80.0%) (Kwan et al, 2009;Li et al, 2009). The vast majority of students consented to HPV vaccination after 13 years and 38.0% of males and 50.7% of females suggested an age over 19 years.…”
Section: Discussionmentioning
confidence: 74%
“…Existing studies have shown that knowledge about HPV may strongly influence vaccination acceptance (Gerend et al, 2007;Gottvall et al, 2009). In China, there have been some studies examining this topic, both in Hong Kong Kwan et al, 2008;Kwan et al, 2009) and in mainland China Zhang et al, 2013). The study populations assessed in these studies have included women, adolescent girls, parents, government officials, and medical personnel.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in contrast with other studies where vaccination acceptance was significantly associated with higher number of sexual partners, (Hoover et al 2000). Other studies concluded that partner's approval, history of gynaecological disease, and one's mother having experienced cancer, increased acceptance of HPV vaccination (Marlow et al, 2007;Hsu et al, 2009;Kwan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,14,16,23,24) Since most of the research participants showed a lack of knowledge in HPV, they also displayed poor knowledge about HPV vaccination and its preventable effects on cervical cancer. 8,14,16,18,[23][24][25] Across six studies, only 6-48% of women knew that HPV can cause cervical cancer 8,14,20,23,25,26) and approximately 19-31.5% of participants were aware of the sexually transmitted nature of HPV infection and its connection to cervical cancer. 8,16,25) Levels and measure of HPV and HPV vaccine varied greatly across the studies.…”
Section: Knowledge Of Hpv and Hpv Vaccinationmentioning
confidence: 99%
“…However, this could be different in Asian countries since cultural belief, family and social norm toward STDs and its prevention are different. [14][15][16] The purpose of this review is to provide a summary of findings from studies of attitudes and knowledge about HPV and HPV vaccination, and actual uptake studies that have been performed in Asian countries.…”
Section: Introductionmentioning
confidence: 99%